KINERJA EFISIENSI KANTOR PELAYANAN PAJAK PRATAMA:PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Hendra Triantoro; Bambang Subroto (Jurnal Akuntansi Aktual, 2016)
Abstract: This research aims to assess the technical efficiency performance of Small Taxpayer Office(KPP Pratama) in the Regional Tax Office of East Java III, during 2011-2014, uses Data EnvelopmentAnalysis (DEA) approach. Input variables are spending, the number of Account Representative, and thenumber Tax Auditor, while tax revenues are selected as output variable. The results showed that therewere four units Small Taxpayer Office, that are more efficient compared to other units. Reallocation ofinput resources are needed to improve the efficiency pf the other units.Keywords: efficiency, Data Envelopment Analysis (DEA), Small Taxpayer Office